FAKTOR PENENTU NILAI TAMBAH BRUTO PADA KONSUMSI WISATAWAN DAN PENYERAPAN TENAGA KERJA DI INDONESIA - Entaresmen, R. Ajeng; Usman, Wan; Husin, Zulkifli; Hamzah, Muhammad Zilal (Proceeding SENDI_U, 2015)
The tourism industry has grown to become one of the largest industries in the world. Indonesiantourism can flourish, generating income for the state and also employment opportunities. Thepurpose of this study is to calculate the impact of the consumption of tourists jointly to the grossvalue added and employment in Indonesia in the period 2008-2012.This study used secondary,secondary data obtained from the data in Table input output (IO) issued by BPS form 2005updated IO data 2008. The impact of the consumption of tourists, the largest is the restaurantand hotel. The impact of tourist consumption can create jobs in the period 2008 - 2012approximately three million people per year.Keywords: tourist consumption, Gross Value Added, employment